INGLIZ TILI VA AXBOROT TEXNOLOGIYALARINI INTEGRATSIYALASHNING TA’LIMDAGI AHAMIYATI (International journal of artificial intelligence, 2026)
This article examines the scientific and methodological significance of integrating English language education and information technology in the modern educational process. English is considered a means of global communication that expands learners’ access to international information resources, while information technology serves as a tool for organizing interactive, flexible, and individualized learning. The article discusses digital learning, mobile applications, online platforms, artificial intelligence tools, teachers’ technological-pedagogical competence, and learners’ independent learning skills. Possible challenges, including distraction, insufficient digital literacy, and unequal access to technology, are also analyzed, and methodological recommendations are proposed.